Bartter Syndrome Type 3: Phenotype-Genotype Correlation and Favorable Response to Ibuprofen - Yang, Xuejun; Zhang, Gaofu; Wang, Mo; Yang, Haiping; Li, Qiu (Frontiers in Pediatrics, 2018)
Objective To identify the causative mutations and investigate phenotype-genotype correlations in two children diagnosed with Bartter syndrome type 3. Methods Phenotype and genotype data from two patients were analyzed and indicated continuous abnormal electrolyte disturbance, metabolic alkalosis, and growth retardation. Their progress was compared after follow-up for different periods (6 and 2 years in each case). Results Mutation analysis of CLCNKB revealed that one patient carried compound heterozygous mutations in this gene including a transition (A to G) at the -2 position of the splicing acceptor site of intron 12 (NM_000085.4:C.1228-2A>G), which may result in abnormal splicing of exon 12, and a loss of exons 1–18 (NM_000085.4: Ex1_18 del), while the other had a homozygous deletion (NM_000085.4: Ex1_18 del) inherited from consanguineous parents. Comprehensive therapy with ibuprofen, antisterone, captopril, and potassium was remarkably effective in treating the patients, and ibuprofen appeared to partly overcome growth retardation in the case with compound heterozygous mutation of CLCNKB. Conclusion Bartter syndrome should be considered as a diagnosis for children with continuous abnormal electrolyte disturbance, metabolic alkalosis, and growth retardation. The clinical features of this genetic disease depend on the type of underlying mutation. Bartter syndrome can be ameliorated by electrolyte supplementation, prostaglandin synthetase inhibitors, angiotensin-converting enzyme inhibitors, and potassium-sparing diuretic. As associated phenotypes include electrolyte disturbances, infections, growth retardation, kidney failure, and even death, Bartter syndrome requires lifelong treatment, and early diagnosis and treatment are critical.